1995
DOI: 10.1291/hypres.18.209
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in 24-h Blood Pressure Pattern of Young Normotensive Women.

Abstract: To investigate the seasonal variations in ambulatory blood pressure patterns, 24-h blood pressure was measured every 15 minutes noninvasively in ten young normotensive women. Urine was collected every 4 hours. The examinations were repeated in spring, summer, autumn, and winter in a standardized living environment.The 24-h average systolic and diastolic blood pressures did not differ significantly among the seasons. Similarly, there were no significant differences in the average values of either daytime or nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
1
12
0
1
Order By: Relevance
“…To control for potential seasonal effects, this study was conducted from March to June 2005, a time of year that Taipei temperatures range between 18 and 24 °C. 16,17 Twenty-four hour monitoring of arterial BP. The ABPM was recorded with a noninvasive, automated oscillometric device, Dynapulse 5000A (Pulse Metric, San Diego, CA).…”
Section: Dynamic Bp Changes Work Shifts and Recoverymentioning
confidence: 99%
“…To control for potential seasonal effects, this study was conducted from March to June 2005, a time of year that Taipei temperatures range between 18 and 24 °C. 16,17 Twenty-four hour monitoring of arterial BP. The ABPM was recorded with a noninvasive, automated oscillometric device, Dynapulse 5000A (Pulse Metric, San Diego, CA).…”
Section: Dynamic Bp Changes Work Shifts and Recoverymentioning
confidence: 99%
“…Previous studies have also reported a seasonal variation in casual, home and 24-h BP with a 2-4 mm Hg higher BP during winter, and a trend towards higher BP during winter was also found in our study. [32][33][34][35][36][37][38][39][40] However, no seasonal effect on BP response to change in dietary salt intake was found. Thus, salt sensitivity classification did not seem to be influenced by season.…”
Section: Methodology Of Salt Sensitivity Testingmentioning
confidence: 89%
“…As previously reported by others, a sea-382 sonal effect on daily sodium excretion and diuresis was found. [30][31][32] But time of year did not influence the response of daily sodium excretion following change in dietary salt intake. Previous studies have also reported a seasonal variation in casual, home and 24-h BP with a 2-4 mm Hg higher BP during winter, and a trend towards higher BP during winter was also found in our study.…”
Section: Methodology Of Salt Sensitivity Testingmentioning
confidence: 99%
“…These definitions were used because the acrophase of the BP was approximately at 1500 hours. 15 Because some participants measured the HBP twice or more, while others measured it only once, the HBP values of the first measurement were used for the calculations. Data revealing unfitness of the arm-cuff or movement during the measurement were excluded.…”
Section: Methodsmentioning
confidence: 99%